Pengaruh Obesitas dan Perokok terhadap Kejadian Post Operative Nausea and Vomiting pada General Anestesi - Mustopa, Ahmad; Al Husaini, Jamilah; Munawaroh, Madinatul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify the influence of obesity and smoking on the incidence of PONV in general anesthesia patients. This research method is a type of quantitative research with analytical observational type, using a cross sectional design. The sampling technique used was non-probability sampling with purposive sampling, namely 68 respondents were obtained. The data measurement tools used were Gordon score observation sheets, smoking habits questionnaires, and interviews. The statistical test used is Spearman's Rank. The results of the study showed that from 68 respondents, for obesity, the number of underweight BMI respondents was 4 respondents, 5.9% and for smoking habits, namely passive smoking, 42 respondents, 61.8%. Obesity with a p value of 0.000 < 0.05 means there is a significant influence between obesity and PONV. Smokers with a p value of 0.942 > 0.05 means there is no significant influence between smokers and PONV. Conclusion, Based on the results of research conducted regarding the influence of obesity and smoking on the incidence of post-operative nausea & vomiting (PONV) in general anesthesia at Sumedang District Hospital. Keywords: General anesthesia, Obesity, Smoker, Post Operativ Nausea and Vomiting